Using Behavioral Consensus to Learn about Social Conventions in Early Childhood - Zhao, Wanying; Baron, Andrew S.; Hamlin, J. K. (Frontiers in Psychology, 2016)
Adults make inferences about the conventionality of others’ behaviours based on their prevalence across individuals. Here, we look at whether children use behavioural consensus as a cue to conventionality, and whether this informs which cultural models children choose to learn from. We find that 2- to 5-year old children exhibit increasing sensitivity to behavioural consensus with age, suggesting that like adults, young humans use behavioural consensus to identify social conventions. However, unlike previous studies showing children’s tendencies to prefer and to learn from members of a consensus, the present study suggests that there are contexts in which children prefer and learn from unconventional individuals. The implications of these different preferences are discussed.